A prospective cohort register-based study of chronic postsurgical pain and long-term use of pain medication after otorhinolaryngological surgery - Graf, Nina (Sci Rep, 2021)
Data on chronic postsurgical pain (CPSP) after otorhinolaryngological surgery are sparse. Adult in-patients treated in 2017 were included into the prospective PAIN OUT registry. Patients’ pain on the first postoperative day (D1), after six months (M6) and 12 months (M12) were evaluated. Determining factor for CPSP was an average pain intensity ≥ 3 (numeric rating scale 0–10) at M6. Risk factors associated with CPSP were evaluated by univariate and multivariate analyses. 10% of 191 included patients (60% male, median age: 52 years; maximal pain at D1: 3.5 ± 2.7), had CPSP. Average pain at M6 was 0.1 ± 0.5 for patients without CPSP and 4.2 ± 1.2 with CPSP. Average pain with CPSP still was 3.7 ± 1.1 at M12. Higher ASA status (Odds ratio [OR] = 4.052; 95% confidence interval [CI] = 1.453–11.189; p = 0.007), and higher minimal pain at D1 (OR = 1.721; CI = 1.189–2.492; p = 0.004) were independent predictors of CPSP at M6. Minimal pain at D1 (OR = 1.443; CI = 1.008–2.064; p = 0.045) and maximal pain at M6 (OR = 1.665; CI = 1.340–2.069; p < 0.001) were independent predictors for CPSP at M12. CPSP is an important issue after otorhinolaryngological surgery. Better instrument for perioperative assessment should be defined to identify patients at risk for CPSP.